2020
DOI: 10.3390/biom10081154
|View full text |Cite
|
Sign up to set email alerts
|

Not So Slim Anymore—Evidence for the Role of SUMO in the Regulation of Lipid Metabolism

Abstract: One of the basic building blocks of all life forms are lipids—biomolecules that dissolve in nonpolar organic solvents but not in water. Lipids have numerous structural, metabolic, and regulative functions in health and disease; thus, complex networks of enzymes coordinate the different compositions and functions of lipids with the physiology of the organism. One type of control on the activity of those enzymes is the conjugation of the Small Ubiquitin-like Modifier (SUMO) that in recent years has been identifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 119 publications
(197 reference statements)
0
4
0
Order By: Relevance
“…Some evidence shows that F. nucleatum activates NF‐ κ B in CRC cells, while activated NF‐ κ B has been reported to upregulate CPT1B. [ 24 ] Thus, we hypothesized that F. nucleatum elevated CPT1B expression, likely through activation of NF‐ κ B. Consistent with previous reports, we observed that F. nucleatum infection indeed activated NF‐ κ B in CRC cells as well as CCSCs through the TLR4/MyD88 axis (Figure S6A , Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some evidence shows that F. nucleatum activates NF‐ κ B in CRC cells, while activated NF‐ κ B has been reported to upregulate CPT1B. [ 24 ] Thus, we hypothesized that F. nucleatum elevated CPT1B expression, likely through activation of NF‐ κ B. Consistent with previous reports, we observed that F. nucleatum infection indeed activated NF‐ κ B in CRC cells as well as CCSCs through the TLR4/MyD88 axis (Figure S6A , Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…In fact, CPT1B has been reported to be regulated by NF‐ κ B through SUMO specific protease 2 (SENP‐2), while FASN is regulated by sterol regulatory element binding proteins (SREBPs), which are targets of NF‐ κ B. [ 24 , 30 ] To this end, NF‐ κ B regulates different metabolic genes in CCSCs and regular CRC cells, thereby mediating distinct lipid metabolisms.…”
Section: Discussionmentioning
confidence: 99%
“…Cytochrome P450 (CYP) monooxygenases were significantly related to cholestasis and DHXSD treatment. According to previous research, CYP enzymes play a key role in the biotransformation of xenobiotics (alcohol, drugs, carcinogens, and environmental pollutants) and endobiotic compounds (steroids, fatty acids, and bile acids) ( 40 ). Among the DEGs, CYP8B1 plays a vital role in the ratio of primary bile salts, which might provide clues about the evolution of the bile pathway ( 41 ).…”
Section: Discussionmentioning
confidence: 99%
“…Cardiovascular disease (CVD) has been the main threat to human life and health, causing high morbidity and mortality around the world. , Atherosclerosis (AS), as one of the primary causes of CVD, is a chronic and progressive inflammatory vascular disease characterized by formation of plaques containing numbers of inflammatory cells and lipids in the arterial wall. A large lipid core and a high inflammatory cell content are the main factors for vulnerable plaque formation. The influx of lipids and infiltration of inflammatory cells in atherosclerotic plaque rely on vasa vasorum for transport. , With the development of plaque, abundant vasa vasorum are formed to maintain the transportation of materials and nutrients .…”
Section: Introductionmentioning
confidence: 99%